DEVELOPMENT OF HADITH SCIENCE IN THE 9TH CENTURY (The Journal of Interdisciplinary Human Studies, 2026)
This article discusses the scientific environment of the ninth century in the history of Islam and its development processes.  At the same time, the acceleration of the science of hadith, which is the second main source of religion, and the period when the authentic and reliable ones were separated from the weak, fabricated hadiths, that is, the golden age of the science of hadith, are discussed.
Keywords: “Bayt al-Hikma”, “Ulum al-Hadith”, “Mu’tazila”, “Mihna”, Shihab az-Zuhri, Abu Abdurahman an-Nasai.